2024
DOI: 10.1007/s13384-024-00698-0
|View full text |Cite
|
Sign up to set email alerts
|

I belong; hence, I engage? A cohort study of transitions between school engagement classes and academic achievement: The role of relational school climate

Ioannis Katsantonis

Abstract: The role of the school climate in buffering disengagement remains relatively underresearched. The present study examined transitions between classes of early adolescents’ school engagement and relational school climate factors influencing classes of students’ (dis-)engagement, and how these were linked with academic achievement in mid-adolescence. A representative sample of 3,643 early adolescents (48.72% females) from the Growing Up in Australia cohort study was utilised. Latent transition analyses indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…School disengagement in adolescents is typically associated with rises in problematic externalising behaviours (Skinner & Pitzer, 2012). However, such declines in engagement are not universally observed and some groups of adolescents may be at greater risk than others (Katsantonis, 2024), particularly those that lack the encouragement from parents or those households that do not have the resources or time to address challenging developmental behavioural changes (Salmela-Aro et al, 2021).…”
Section: What Are the Main Insights That The Paper Provides?mentioning
confidence: 99%
“…School disengagement in adolescents is typically associated with rises in problematic externalising behaviours (Skinner & Pitzer, 2012). However, such declines in engagement are not universally observed and some groups of adolescents may be at greater risk than others (Katsantonis, 2024), particularly those that lack the encouragement from parents or those households that do not have the resources or time to address challenging developmental behavioural changes (Salmela-Aro et al, 2021).…”
Section: What Are the Main Insights That The Paper Provides?mentioning
confidence: 99%
“…Holding greater levels of motivation has been linked with a manifold of positive outcomes, such as well-being ( Howard et al, 2021 ), greater productivity ( Cerasoli et al, 2014 ), and greater self-esteem ( Tang et al, 2020 ). Nevertheless, research studies on adolescent students’ motivation and engagement in secondary schools have shown that students’ motivation and engagement are also declining ( Wang and Eccles, 2013 ; Katsantonis and McLellan, 2023b ; Katsantonis, 2024 ).…”
Section: Introductionmentioning
confidence: 99%